Preface to Special Issue on Digital Twin Empowered Internet of Intelligent Things for Engineering Cyber-Physical Human Systems - Venkatesan, C.; Zhang, Yu-Dong; Xin, Qin (Computer Assisted Methods in Engineering and Science, 2023)
This special issue entitled Digital Twin Empowered Internet of Intelligent Things for Engineering Cyber-Physical Human Systems contains a collection of selected papers all discussing the state-of-the-art cyber-physical human systems, artificial intelligence techniques, biomedical engineering and optimization algorithms. All the articles published in this special issue were accepted for publication after a careful peer-review process to fulfill the standard quality requirements and fall within the journal’s scope.